Food Insecurity and Eating Behavior Relationships Among Congregate Meal Participants in Georgia. Issue 1 (2nd January 2016) - Myles, TaMara; Porter Starr, Kathryn N.; Johnson, Kristen B.; Sun Lee, Jung; Fischer, Joan G.; Ann Johnson, Mary
ABSTRACT: This study explored relationships of food insecurity with cognitive restraint, uncontrolled eating, and emotional eating behaviors among congregate meal participants in northeast Georgia [ n = 118 years, age 60 years and older, mean (SD) age = 75 (8 ) years, 75% female, 43% Black, 53% obese (Body Mass Index ≥ 30)]. Food insecurity was assessed with a 6-item questionnaire. Scores ranged from 0 to 6 and were defined as high or marginal food security, FS, 0–1 (70%); low food security, LFS, 2–4 (20%); very low food security, VLFS, 5–6 (10%); and low and very low food security, LVLFS, 2–6 (30%). Eating behavior was assessed with an 18-item Three-Factor Eating Questionnaire R-18. In bivariate analyses food insecurity was consistently associated with cognitive restraint scores above the median split and to a lesser extent with uncontrolled eating scores ( p ≤ 0.05). No association was found between emotional eating and food insecurity. In multivariate linear and logistic regression analyses, food insecurity was consistently associated with cognitive restraint ( p ≤ 0.05) even when controlled for potential confounders (demographics, Body Mass Index, and chronic diseases). Food insecurity was also associated with uncontrolled eating ( p ≤ 0.05), but the relationship was attenuated when controlled for potential confounding variables. Although cognitive restraint is defined as the conscious restriction of food intake to control body weight or promote weight loss, these findings suggest there may be other dimensions of cognitive restraint to consider in nutritional assessment and interventions among food-insecure older adults.